Other lives: mind and world in Indian Buddhism - Kachru, Sonam (Columbia University Press, 2021)
"Human experience is not confined to waking life. Do experiences in dreams matter? Humans are not the only living beings who have experiences. Does nonhuman experience matter? The Buddhist philosopher Vasubandhu, writing during the late fourth and early fifth centuries C.E., argues in his work The Twenty Verses that these alternative contexts ought to inform our understanding of mind and world. Vasubandhu invites readers to explore experiences in dreams and to inhabit the experiences of nonhuman beings-animals, hungry ghosts, and beings in hell. Other Lives offers a deep engagement with Vasubandhu's account of mind in a global philosophical perspective. Sonam Kachru takes up Vasubandhu's challenge to think with perspective-diversifying contexts, showing how his novel theory draws together action and perception, minds and worlds. Kachru pieces together the conceptual system in which Vasubandhu thought to show the deep originality of the argument. He reconstructs Vasubandhu's ecological concept of mind, in which mindedness is meaningful only in a nexus with life and world, to explore its ongoing philosophical significance. Engaging with a vast range of classical, modern, and contemporary Asian and Western thought, Other Lives is both a groundbreaking work in Buddhist studies and a model of truly global philosophy. The book also includes an accessible new translation of The Twenty Verses, providing a fresh introduction to one of the most influential works of Buddhist thought"--